"We can Shapeshift and Build Bridges": Bisexual Women and Gender Diverse People of Color on Invisibility and Embracing the Borderlands. Issue 2 (3rd April 2019) - Ghabrial, Monica A.
Abstract: Bisexual women and gender diverse people of Color (biWGDPoC) challenge many traditional notions of gender, sexuality, and race, possessing identity categories that enable them to blend with different groups and communities. Although this invisibility grants safety in some contexts, it may also be a source of stress. The present study involved thematic analysis of qualitative survey responses from biWGDPoC, in which participants discussed passing and visibility. Notable themes included invisibility at the intersections of sexual, gender, and ethnoracial identity; skin tone and biracial identity; the exacerbated isolation that results from lack of heritage language; feelings of identity betrayal when dating (White) cisgender men; and biWGDPoC-specific challenges. Novel positive perspectives on identity invisibility also emerged, in which participants discussed finding privilege in fluency and using their ability to pass to advocate for others. Throughout these topics, participants note femininity as a factor in (in)visibility, as well as notions of falsehood and diminished self-worth.